Insights : readings in strategic management - Hitt, Michael A.; Ireland, R. Duane; Hoskisson, Robert E. (Cincinnati, OH : South-Western College, 1999)
Navigating in the New competitive landscape, academy of Mgt executive. Compaq to acquire digital once an unthinkable deal, WSJ. Creating a great E-Commerce business, fortune. Read your history, Janet, Forbes. From steer to eternity, Inc. tech. Competitive advantage and internal organizational assessment...
Keywords: Management; Strategic planning; Strategic planning